Publicidade, tecnologia e sociedade de consumo: uma análise de peças publicitárias na Revista Veja - Fernandes, Alessandra Lemos de Oliveira (2012)
This research presents the results of a study that analyzed the representations of technology in select advertising on Veja, the biggest weekly Brazilian magazine with over one million readers per month. Based on the methodology of French Discourse Analysis it was observed that is the discourse of publicity about technological devices goes beyond the usefulness of the object itself, but also aiming to sell a lifestyle, promising better social status generated by consumption. It was analyzed advertisements published in the decades from 1970 to 2000, during in which there were permanent strategies that offer technology assets by combining them with concepts of progress, increased productivity among employees and the need for replacement of the apparatus of appliances and products said the most modern and innovative. To support the reading, it was used concepts of thinkers such as Jean Baudrillard (1995), Zygmunt Bauman(2007 e 2008), Robert Sennett (1999), Naomi Klein (2003 e 2006), Milton Santos (2000) and Andrew Feenberg (2010, 2003, 1995 e 1991) about technology, society, technology, consumption and the use of advertising in today's society to analyze how advertisings available by Veja magazine.